2010
DOI: 10.1152/ajpgi.00357.2010
|View full text |Cite
|
Sign up to set email alerts
|

Regional differences in colonic mucosa-associated microbiota determine the physiological expression of host heat shock proteins

Abstract: Cytoprotective heat shock proteins (Hsps) are critical for intestinal homeostasis and are known to be decreased in inflammatory bowel diseases. Signals responsible for maintenance of Hsp expression are incompletely understood. In this study, we find that Hsp25/27 and Hsp70 protein expressions are differentially regulated along the longitudinal length of the large intestine, being highest in the proximal colon and decreasing to the distal colon. This longitudinal gradient was similar in both conventionally colo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
52
2

Year Published

2011
2011
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(56 citation statements)
references
References 38 publications
2
52
2
Order By: Relevance
“…Experiments in rodents and humans have shown that expression of intestinal HSP25/27 and HSP72 is dependent on the presence of gut microbiota (19,26). In a striking difference to our results, those studies found that the proximal colonic mucosa exerted the strongest HSP25/27 and HSP72 expression, due to the highly diversified and dense bacteria population.…”
Section: Microbiota Complexity Varies In Different Regions Of Porcinecontrasting
confidence: 99%
See 3 more Smart Citations
“…Experiments in rodents and humans have shown that expression of intestinal HSP25/27 and HSP72 is dependent on the presence of gut microbiota (19,26). In a striking difference to our results, those studies found that the proximal colonic mucosa exerted the strongest HSP25/27 and HSP72 expression, due to the highly diversified and dense bacteria population.…”
Section: Microbiota Complexity Varies In Different Regions Of Porcinecontrasting
confidence: 99%
“…Indeed, microbiota is one of the major determinants of HSP expression in IECs, as has been clearly demonstrated in antibiotic-treated mice, in which HSP25 and HSP72 are significantly reduced in the colonic mucosa (26). Moreover, HSP expression is absent in the gut of germ-free mice (19). An unexpected finding in the present study was that the distal ileal mucosa in pigs exhibited stronger expression of both HSPs than the proximal colon.…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…Based on the current experimental data, it seems that HSPs are key elements in the type of immune system responsiveness or reactivity that is induced by the following three typical conditions: one, sterile tissue damage, when tissue-derived HSPs in combination with DAMPs activate tissue repair and regulation; two, damage caused by infectious pathogens, when HSPs in the presence of DAMPs and pathogen-derived PAMPs lead to a full proinflammatory response with elimination of infection and regulation; and three, homeostatic interactions with commensal symbionts of the gut microbiota, when a combination of PAMPs and HSPs leads to the regulation and maintenance of symbiosis [22][23][24] . Given the ubiquitous presence and stressinducible nature of HSPs in both tissue cells and microbial invaders or symbionts, therapeutic targeting of HSPs offers an attractive possibility for the fine-tuning of such immune responses and the dampening of inflammation through the induction or activation of regulatory T cells.…”
mentioning
confidence: 99%